1985
DOI: 10.1152/ajprenal.1985.249.2.f263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KCl infusion on potassium excretion in sheep

Abstract: To determine the quantitative relation of K excretion (UKV) to plasma K concentration (PK), three fasted, conscious, mature ewes were infused intravenously with 50 mmol KCl over 15, 30, and 60 min. Control experiments were without infusion. During KCl infusion PK was increased to 7.26 +/- 0.40 (15 min), 6.68 +/- 0.48 (30 min), and 5.59 +/- 0.3 meq/liter (60 min). During all three infusions the increase in UKV relative to the increase in PK was similar. The mean delta UKV/delta PK ratio was 160 +/- 30 (SD) mueq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…C and D: data from individual rats are shown with open symbols representing the 0% K ϩ diet group, and solid symbols the 1% K ϩ diet group (n ϭ 2 and 3, respectively). Rabinowitz (24,25) previously compared renal K ϩ excretion in sheep following a typical meal vs. K ϩ excretion during intravenous K ϩ infusion in the fasting state that reproduced meal-induced rises in plasma [K ϩ ]. He found that K ϩ excretion with intravenous infusion was only ¼ the amount observed with meal intake, concluding that meal-induced increases in renal K ϩ excretion cannot be explained by changes in plasma [K ϩ ].…”
Section: R425mentioning
confidence: 99%
See 2 more Smart Citations
“…C and D: data from individual rats are shown with open symbols representing the 0% K ϩ diet group, and solid symbols the 1% K ϩ diet group (n ϭ 2 and 3, respectively). Rabinowitz (24,25) previously compared renal K ϩ excretion in sheep following a typical meal vs. K ϩ excretion during intravenous K ϩ infusion in the fasting state that reproduced meal-induced rises in plasma [K ϩ ]. He found that K ϩ excretion with intravenous infusion was only ¼ the amount observed with meal intake, concluding that meal-induced increases in renal K ϩ excretion cannot be explained by changes in plasma [K ϩ ].…”
Section: R425mentioning
confidence: 99%
“…Thus, the maintenance of K ϩ homeostasis has been traditionally understood on the basis of the concept of negative feedback control. However, Rabinowitz (21,22) challenged this traditional view when he pointed out that plasma K ϩ and aldosterone can stimulate renal K ϩ excretion only at levels above their normal ranges (3,25,31,32). In his studies in the sheep (24), meal intake over 1 h produced a pronounced kaliuresis, which occurred in the absence of a change in plasma aldosterone concentration and with only a very small (0.5 meq/l) increase in plasma [K ϩ ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rabinowitz (16,17) challenged this traditional view. He pointed out that plasma K ϩ and aldosterone can stimulate renal K ϩ excretion only at levels above their normal ranges (2,19,23,24). In his studies in the sheep (18), meal intake produced a pronounced kaliuresis, which was accompanied by no change in plasma aldosterone concentration.…”
mentioning
confidence: 99%
“…It was reported that aldosterone can contribute to U K V only under the condition of supraphysiologic levels due to hyperkalemia. 25 In addition, recently, it was reported that dietary potassium intake was sensed in the gut, and an unidentified gut factor is activated to stimulate renal potassium. 26 Dietary potassium was constant and relatively low in this study protocol.…”
Section: Discussionmentioning
confidence: 99%